GOLD report on the diagnosis and management of COPD. Issue 2 (February 2017) - Mayor, Susan
Abstract : The new Global Initiative for Chronic Obstructive Lung Disease (GOLD) report on the prevention, diagnosis and management of COPD advises using inhaled steroids less frequently than in current practice. This article summarises the main recommendations of the report and the implications for GPs.